Effects of speed, agility, and quickness training on athletic performance: a systematic review and meta-analysis - Sun, Min; Soh, Kim Geok; Cao, Shudian; Yaacob, Azhar; Ma, Shuzhen; Ding, Cong (BioMed Central Ltd, 2025)
Background: Previous studies have demonstrated the effects of SAQ training on sprint, change-of-direction, and jump performance in soccer players. However, further research is needed to assess its broader impact on different athletic populations and performance metrics. This study aims to expand the existing evidence by incorporating a wider range of outcomes and providing a more comprehensive analysis of SAQ training effects. Methods: A thorough search of databases, including Web of Science Core, SPORTDiscus, PubMed, and SCOPUS, was conducted, with data up to July 2024. The PEDro scale assessed study quality and RevMan 5.3 evaluated bias risk. Effect sizes (ES) were calculated from means and standard deviations, with heterogeneity assessed using the I² statistic. Publication bias was evaluated using an extended Egger test. Results: Eleven RCTs involving 499 healthy athletes from sports such as soccer, basketball, tennis, and handball met the inclusion criteria. The SAQ interventions lasted between 4 and 12 weeks, with a frequency of two to three sessions per week. The analysis revealed significant improvements in 5-meter sprint (ES = 0.63, p < 0.01), 20-meter sprint (ES = 0.49, p < 0.01), 30-meter sprint (ES = 0.55, p = 0.015), change of direction (COD) performance (ES = 0.39, p < 0.01), reaction time (ES = 0.52, p = 0.01), lower limb power (ES = 0.96, p < 0.01), and flexibility (ES = 0.57, p < 0.01), with effect sizes ranging from small to moderate. Subgroup analysis indicated that only session duration had a near-significant effect on COD performance (≤ 60 min: ES = 0.58; >60 min: ES = 0.24; p = 0.059). Conclusions: SAQ training effectively enhances sprint performance, COD ability, reaction time, lower limb strength, and flexibility, with effect sizes ranging from small to moderate. The findings suggest that shorter training durations (≤ 60 min) may be more beneficial for improving COD performance, although this effect did not reach statistical significance. Further trials are recommended to determine the optimal training dosage, along with high-quality studies covering a broader range of sports, particularly in athletes aged 14 to 18.